Cancer risk among young men with weight gain after smoking cessation: A population-based cohort study. (June 2019) - Kim, Kyuwoong; Choi, Seulggie; Lee, Gyeongsil; Jeong, Su-Min; Kim, Sung Min; Son, Joung Sik; Yun, Jae-Moon; Kim, Yeon-Yong; Park, Seong Yong; Park, Sang Min
Highlights: Weight gain associated with smoking cessation may attenuate the protective effect of smoking cessation with cancer. Young men are advised to abstain from cigarette smoking to reduce the disease burden of cancer. Lifestyle modification to minimize weight gain associated with smoking cessation should be considered among quitters. Abstract: Background: Smoking cessation may help the current smokers to reduce cancer risk. However, weight gain following smoking cessation may attenuate the protective association of cessation with cancer. Patients and methods: Our study included 1, 278, 794 men who were aged 20–39 years and underwent two consecutive health examinations by the National Health Insurance Service, without previous diagnosis of cancer. Participants were categorized into continual smokers, quitters with different degree of body weight change, and never smokers based on the biennial national health screening program (2002–2003 and 2004–2005) and were followed from January 1, 2006 to December 31, 2015. Cox proportional hazard models and restricted cubic spline model was used to evaluate the association of post-cessation weight change and cancer risk after adjustment for potential confounders. Results: During the 10 years of follow-up, the analyses included 1, 278, 794 men with 21, 494 cancer incidences. Compared to continual smokers, quitters without weight gain of 2.0 kg had significantly lower risk of obesity-related cancer (hazard ratio [HR], 0.88; 95% confidence interval [CI], 0.79-0.97), smoking-related cancer (HR, 0.90; 95% CI, 0.83 to 0.98), and gastrointestinal cancer (HR, 89; 95% CI, 0.80 to 0.98). Weight gain among quitters attenuated the risk reduction of cancer compared to continual smoking. Among quitters, weight gain up to 5.0 kg with smoking cessation showed protective association with cancer risk among quitters without weight gain. Conclusion: Excessive weight gain with smoking cessation among quitters was not associated with reduced risk of several cancer types. This association should be taken into account when recommending smoking cessation to prevent cancer